(3QSGdI aj JMQjQ hRf GdeKbGd hGdOQges - (3GHf GdQaYI , CMeO Hf eMeO Hf Ydj GdTGaYj GdeUQj GdCfUGQj, GHf GdQaYI,J (B710 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeg GdeJhGdjI Ydi eQ GdReGf hGdeGfM CgdgG HeG ajg bhGe GdOjf s
(3BNQgG (B:s
(3efg HJQcjH dCfg jSY ef MH s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B135s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3QjGVg JjehQ (B359) s
Keywords: (3GdQjGVjGJs